Mark. - Jacobsen, David Schnasa (Fortress biblical preaching commentaries., 2014)
David Schnasa Jacobsen draws together the strengths of two exegetical approaches to the Gospel of Mark in this volume of the Fortress Biblical Preaching Commentaries series. Jacobsen takes a broad thematic approach to the first Gospel, while at the same time giving exegetical and homiletical insights about individual periscopes in their narrative context. By helping preachers and students make connections between the various lections from Mark throughout Year B in their sermons and studies, they and their parishioners will have a deeper appreciation of Mark's unique interpretation of the Christ Event and how that influences their approach to living the Christian faith in today's world. With liturgical sensitivity and exegetical skill, Jacobsen provides a unique preaching resource that will build biblical literacy by assisting both preachers and listeners in understanding Mark's Gospel as narrative-theological whole, not just as a collection of loosely related stories.